Economic Empowerment of the Coastal Society: A Case Study of Ujoeng Pacu Village, Muara Satu District, Lhokseumawe - Aceh - Nirzalin Nirzalin (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2019)
The various policies of the Indonesian government in the maritime sector have objectively succeeded in increasing the production and export value of the Indonesian fish trade in the world. The 2017 statistics, for example, show Indonesia's exports in the fisheries sector reached 979,910 tons of fish with a value of 4.09 billion US dollars. However, the amount of income in the fisheries sector only succeeded in making prosperous capital owners (toke) and contractors who obtained various infrastructure development projects. Fishermen and coastal communities actually remain in poverty. In 2017, 34% of fishermen and coastal communities were in poverty. The process of strengthening the welfare of fishermen and coastal communities can actually be done through economic empowerment programs by involving mentoring from academics across scientific disciplines. Based on the case of the empowerment of the coastal community of Ujoeng Pacu village, Lhokseumawe, this article shows the complexity of reality as well as the success of the Ujoeng Pacu community empowerment process that previously lived in the war economy and the drug economy turned into a productive economy through the cultivation of soft shell crabs and tiger shrimp with polyculture techniques. AbstrakPelbagai kebijakan pemerintah Indonesia di sektor kelautan secara objektif telah berhasil meningkatkan nilai produksi dan ekspor perdagangan ikan Indonesia di dunia. Statistik 2017, misalnya, menunjukkan ekspor Indonesia di sektor perikanan mencapai 979.910 ton ikan dengan nilai 4,09 miliar dolar AS. Namun, jumlah pendapatan di sektor perikanan yang melimpah itu secara objektif pula hanya berhasil memakmurkan pemilik modal (toke)  dan kontraktor yang memperoleh pelbagai proyek pembangunan infrastruktur disektor maritim. Sementara, nelayan dan petani dikawasan  pesisir tetap miskin. Faktanya, pada 2017 pula, 34% masyarakat nelayan dan petani pesisir berada dalam kemiskinan. Proses penguatan kesejahteraan nelayan dan masyarakat pesisir sebenarnya dapat dilakukan melalui program pemberdayaan ekonomi dengan melibatkan pendampingan dari akademisi lintas disiplin ilmu. Berdasarkan kasus pemberdayaan masyarakat pesisir desa Ujoeng Pacu, Lhokseumawe- Aceh, artikel ini menunjukkan bagaimana melalui proses pemberdayaan yang dilakukan secara intensif,  masyarakat Ujoeng Pacu yang sebelumnya hidup dalam ekonomi perang dan ekonomi narkoba perlahan berubah menjadi produktif melalui teknik budidaya polikultur kepiting cangkang lunak (Soka) dan udang windu